Analysis Evacuation Route for KM Zahro Express on Fire Condition using Agent Based Modeling and Fire Dynamics Simulatior - Trika Pitana; Muhammad Badrus Zaman; Dioco Carlos Kristian Perdana; Aleik Nurwahyudi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Safety is the thing that needs to be preferred by users of transport, passengers should also understand about safety procedures and evacuation procedures in the means of transport. There have been many accidents that happen in the world of transport, particularly in the shipping world, from 2010 to 2016 is no more than 50 accidents of ships in accordance with the cause recorded by KNKT (Komisi Nasional Keselamatan Transportasi). On this research was discussed the evacuation time on the ship KM Zahro express that occurred earlier in the year 2017 in the Kepulauan Seribu, DKI Jakarta. Almost all passenger dead caused by fire from power source in engine room. This research explain about evacuation time and dangers from fire that interfere the process of evacuation. The methods used are Agent Based Modeling and Simulation (ABMS) and Fire Dynamics Simulator (FDS) for modeling fire simulation as well as using basic rules which refer to the International Maritime Organization (IMO). Result of Evacuation simulation calculation on normal conditions that match at actually condition is 29,783 minutes, showing the evacuation time is not below the performance standard.